The Red Brigades' Communiqués: An Analysis of the Terrorist Group's Propaganda. Issue 2 (17th February 2020) - Re, Matteo
ABSTRACT: The article analyzes the language, the propaganda, and communication techniques used by the Red Brigades (BR) during their activities. The analysis is based on the study of 181 communiqués, written and circulated by the terrorist organization between 1970 and 1988, i.e., from the beginning to the end of its activities. The corpus comprises three types of communiqués: a) claims of responsibility for violent actions (kidnapping, homicides), b) internal documents aimed at creating a coherent organization and ideology, and c) texts that circulated within the extra-parliamentary Left to generate positive propaganda towards the BR. The paper demonstrates that the language used, as well as the propaganda techniques, underwent important changes during the period of activity of the BR, in accordance with the evolution of their objectives and their internal development. In addition to this, the analysis reveals a certain repetition of specific communication strategies, as well as identification of specific contents that show a certain degree of homogeneity. At the same time, the article also assesses the structural changes that took place within the BR, which may have affected their communiqués.